2020
DOI: 10.1093/ofid/ofaa297
|View full text |Cite
|
Sign up to set email alerts
|

“Myocardial inflammatory changes before and after antiretroviral therapy initiation in people with advanced HIV disease”

Abstract: Because high frequency and late presentation of HIV disease in our population, we decided to explore the presence of myocarditis among people with HIV-infection and advanced immunosuppression (less than 200 CD4+ cells/μL), and to describe the inflammatory changes observed after combined antiretroviral therapy (cART) initiation in an observational, longitudinal, prospective cohort performing cardiovascular MRI (cMRI) and doppler trans-thoracic echocardiogram (TTE).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
(16 reference statements)
0
4
0
Order By: Relevance
“…Thus, it is crucial to identify risk factors associated with the presence of LGE in HIV-infected patients. In addition, few CMR studies ( 17 ) focus on patients in the late stage of HIV disease despite the cardiac complications that occurred more frequently in those patients compared with patients in the early stage. Furthermore, no CMR study to date has assessed the myocardial involvement among the Chinese HIV/AIDS cohort.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is crucial to identify risk factors associated with the presence of LGE in HIV-infected patients. In addition, few CMR studies ( 17 ) focus on patients in the late stage of HIV disease despite the cardiac complications that occurred more frequently in those patients compared with patients in the early stage. Furthermore, no CMR study to date has assessed the myocardial involvement among the Chinese HIV/AIDS cohort.…”
Section: Introductionmentioning
confidence: 99%
“…Sixteen studies involving 5107 participants, 3446 of whom were HIV positive and 1661 were HIV negative, evaluated computed tomographic coronary angiography . Another 16 studies involving 1698 participants, 1203 of whom were HIV positive and 495 were HIV negative, evaluated cardiac MR imaging . Ten studies involving 681 participants, 435 of whom were HIV positive and 246 were HIV negative, evaluated vascular PET scans .…”
Section: Resultsmentioning
confidence: 99%
“…Of the 45 studies, 38 were conducted in high-income countries (49% in the US) with 7 in upper middle-income countries (Figure 1). No studies were performed in low-income countries. The study designs were cross-sectional (85%), prospective cohort (13%), and randomized clinical trial (2%).…”
Section: Resultsmentioning
confidence: 99%
“…While these findings may hint toward the possibility of an immune reconstitution syndrome propagating myocardial inflammation, others have demonstrated the protective effect of ART. 190 Robbertse et al 48 demonstrated a reduction of magnetic resonance imaging–based parameters of myocardial fibrosis (global native T1 times and extracellular volume fraction) following ART initiation with a concurrent improvement in CD4 counts and viral load suppression. Although this study did not assess clinical outcomes, measure myocardial inflammatory cell infiltration, or assess correlations with circulating markers of cardiac injury, it demonstrates 2 important points.…”
Section: Mechanisms Of Coronary Artery Disease In Hiv Infectionmentioning
confidence: 99%